The Impact of Entrepreneurial Strategy on the Firm Performance of Indonesian Technology Startups - Triono, Sunu Puguh Hayu; Rahayu, Agus; Wibowo, Lili Adi; Alamsyah, Andry (Fakultas Ekonomi dan Bisnis, Telkom University., 2024)
Changes in the business environment, driven by technology and globalization, increase the urgency of a strategic orientation for new ventures and, conversely, an entrepreneurial orientation for established firms. Technology startups, as